Characterization of Silk Fibroin Modified Surface: A Proteomic View of Cellular Response Proteins Induced by Biomaterials. (25th March 2014) - Yang, Ming-Hui; Yuan, Shyng-Shiou; Chung, Tze-Wen; Jong, Shiang-Bin; Lu, Chi-Yu; Tsai, Wan-Chi; Chen, Wen-Cheng; Lin, Po-Chiao; Chiang, Pei-Wen; Tyan, Yu-Chang
Abstract : The purpose of this study was to develop the pathway of silk fibroin (SF) biopolymer surface induced cell membrane protein activation. Fibroblasts were used as an experimental model to evaluate the responses of cellular proteins induced by biopolymer material using a mass spectrometry-based profiling system. The surface was covered by multiwalled carbon nanotubes (CNTs) and SF to increase the surface area, enhance the adhesion of biopolymer, and promote the rate of cell proliferation. The amount of adhered fibroblasts on CNTs/SF electrodes of quartz crystal microbalance (QCM) greatly exceeded those on other surfaces. Moreover, analyzing differential protein expressions of adhered fibroblasts on the biopolymer surface by proteomic approaches indicated that CD44 may be a key protein. Through this study, utilization of mass spectrometry-based proteomics in evaluation of cell adhesion on biopolymer was proposed.